Good outcomes after aggressive treatment of immune checkpoint inhibitor related myasthenia gravis: a case series. Issue 6 (27th May 2022) - Weaver, Jamie; Dodd, Katherine; Hameed, Hasan; Roberts, Mark; Lilleker, James; Lorigan, Paul; Cooksley, Timothy
Abstract : Introduction: Myasthenia gravis (MG) is a rare but potentially life-threatening complication of immune- checkpoint inhibitor (ICI) therapy and often co-presents with myositis and myocarditis. We present a series of six patients from a tertiary oncology center. Methods: We reviewed The Christie Hospital database of immunotherapy-related toxicity from 2017–2020. Symptom severity was assessed using the MGFA classification. Results: Six patients with ICI-related MG were identified. The median number of preceding immunotherapy doses was 2. Common initial presenting complaints were ptosis (100%) and diplopia (50%) with 2/6 patients showing severe (MGFA > II) symptoms. Five patients had concomitant myositis and myocarditis. AChR or MuSK autoantibodies were positive in three patients. Two patients required advanced respiratory support. All patients received urgent treatment with intravenous methylprednisolone and mycophenolate. Five also received intravenous immunoglobulin and a single patient was treated additionally with abatacept and rituximab. No patient died from MG-related complications. All were successfully discharged following the acute episode. Discussion: Previous case series of ICI-related MG have reported high mortality rates, particularly in those with overlapping myositis/myocarditis. In our cohort we demonstrate good outcomes associated with early aggressive treatment with IVIG, IVMP, and mycophenolate. An agreed national treatment protocol or clinical discussion forum would be beneficial. jam: weaver75@gmail.com 17